A Qualitative Study on the Policy Process and Development of the National Action Plan on Antimicrobial Resistance in Singapore - Alvin Qijia Chua; Monica Verma; Karen Azupardo; Maria Margarita Lota; Li Yang Hsu; Helena Legido-Quigley (MDPI AG, 2023)
The global public health threat of antimicrobial resistance (AMR) has been accelerated by many interrelated factors spanning across One Health-human health, animal health, and the environment. Singapore launched its own National Strategic Action Plan (NSAP) on AMR in November 2017 with the aim of tackling the growing threat of AMR in Singapore through coordinated approaches. However, little is known about the policy process and development of the NSAP in Singapore. In this study, we analysed these aspects using an AMR governance framework. In-depth interviews were conducted with 20 participants across the One Health spectrum. The interviews were transcribed verbatim and analysed thematically. Areas that were well executed included (1) good coordination across various agencies, (2) a dedicated office to coordinate the work on the NSAP, and (3) a high level of governmental support. Areas that were lacking included (1) a lack of participation from certain sectors, (2) insufficient awareness around the AMR issue, (3) constraints in information sharing, and (4) a lack of ideal indicators to track the progress in addressing AMR. Improvements in these areas will provide a more holistic One Health engagement in support of the effective planning and implementation of the NSAP.